Inheritance and characterization of cooking time, seed iron and zinc content in selected African common bean germplasm - Mukai Mughi, Irene (Makerere University, 2017)
Long cooking time for beans continues to be a major hindrance to the widespread consumption of beans. Prolonged cooking time leads to structural changes at the grain cellular level, resulting in a loss of nutrients such as Iron (Fe) and Zinc (Zn) which are important nutrients in addressing micronutrient malnutrition (“hidden hunger”). The aim of this study was to evaluate the diversity for cooking time, iron and zinc content in a total of 152 genotypes from around eastern Africa, including Kenya, Uganda, Tanzania, Ethiopia, and Rwanda, and to determine the mode of inheritance for cooking time, Fe and Zn content in common bean genotypes. A total of 152 common bean genotypes released by the Pan-Africa Bean Research Alliance (PABRA) across Eastern Africa were planted in the field at International Centre for Tropical Agriculture (CIAT) farm at Kawanda, 13km from Kampala city, during two rainy seasons of 2015 B (April – July) and 2015D (September – December). Data collected included soil nutrient composition for the site used in each season, agronomic data and disease data. Six parental genotypes were crossed in a screen house at CIAT-Kawanda, using a 6 x 6 half diallel mating design. The F1’s were advanced to F2 generation which was subjected to cooking time, Fe and Zn content tests. Cooking time test was carried out at CIAT-Kawanda on plot basis using the standardized Matson cooker method. Fe and Zn analysis was carried out at Rwanda Agricultural Board (RAB) research station in Rubona using the X-Ray Fluorescent (XRF) platform. Across the two seasons, among the 152 genotypes studied, 5 had a cooking time of <45 minutes, 55 genotypes cooked for 46-60 minutes and 92 genotypes cooked for >61 minutes. In response to Fe and Zn seed content, 8.7% were high in Fe (>70 mg/kg) whereas 69.1% were high Zn (>30 mg/kg). A total of 15 genotypes (Amahunja, Awash melka, Bihogo, CAB 2, ECAPAN021, G858, Icaquimbaya, KK20, NABE12C, NABE4, NABE6, ROBA-1, RWR1873, RWV3006) were consistent in short cooking time for the two seasons and had a Fe content above the low Fe check (CAL96 – 55mg/kg). Analysis of variance showed a highly significant variation among genotypes, general combining ability (GCA) and specific combining ability (SCA) components in the F2 for cooking time, Fe and Zn content, indicating that additive variance predominated with non-additive gene effects contributing a considerable amount of variations. Awash melka had the desired GCA combination for cooking time, Fe and Zn content. Significant SCA effect for cooking time and high Fe content were observed in NgwakuNgwaku x KATX56 identifying it as a good cross for combining short cooking with high Fe and Zn content.